Experimental Investigation of Load Settlement Behavior of Coir Mat and Coir Fiber Reinforced Sand - R. Sridhar; M.T. Prathap Kumar (Journal of Natural Fibers, 2018)
An experimental study in terms of model footing test were performed to comparatively assess the effect of form of reinforcement, viz., mat and fiber, on the load intensity response of reinforced sand. Coir reinforcement was used in this present investigation to assess comparative performance of coir mat and coir fiber reinforced sand, as it is highly durable among all other natural materials. Model footing test were conducted by placing coir mat and coir fiber at different u/B ratios. Load deformation behavior was compared with the help of peak strain, bearing capacity ratio and settlement reduction factor. The experimental and calculated theoretical values of peak stress of coir mat reinforced sand were compared and found that both the values were in good agreement with predicted values. The results of the present experimental investigation indicated that the form of reinforcement viz., mat/grid and fibers has significant influence on load deformation behavior of reinforced sand. Coir mat when located within the failure zone intercepting the shear zone below the loaded footing is most beneficial in terms of load carrying capacity of reinforced sand, in consistent with earlier investigations. However maximum increase in bearing capacity of coir fiber reinforced sand does indicate an optimum u/B ratio of 1.0. Maximum SRF for coir mat reinforced sand corresponds to u/B = 0.6 where for coir fiber reinforced sand it corresponds to u/B = 1.0.